Analysis of Mercedes-AMG Petronas F1 Team's Social Media Engagement - S., Raybano Natanael; Iskandar, Budi Permadi (Journal of Business and Management, 2021)
Engagement is an outcome of an interaction between the customer and the company through two-way communication. Social media becomes one of the platforms for the company to perform this kind of interaction. The aforementioned interaction on social media can be measured as “engagement rate”. This study is trying to formulate the role of social media manager in a Formula One team, using the Mercedes-AMG F1 Team as the main example, as the team has a successful social media team that could deliver proper information about the team’s activity and maintain the interaction. This study is done on Twitter, using a content analysis approach and conducted by examining the team’s activity, then comparing it with another chosen Formula One teams, to see how far the team's social media strategy can perform and formulate the strategy itself. The result shows that the Mercedes-AMG F1 Team got its success on social media by consistently sharing team-related contents that attract people and figure out its proper strategy for sharing the contents. These two aspects become the main output of this study, which is formulating one of the most effective ways to maintain an engagement between the company and the customers as high as possible.Keywords: Social Media, Twitter, Engagement, Mercedes-AMG F1 Team, Formula One, Content Analysis